Antidiabetic and antioxidant activities of seed extract from Leucaena leucocephala (Lam.) de Wit - Chowtivannakul, Pichaya; Srichaikul, Buavaroon; Talubmook, Chusri (Agriculture and Natural Resources, 2016)
Leucaena leucocephala (Lam.) de Wit has been used for various purposes such as treatment of stomach diseases, facilitation of abortion, contraception and the treatment of diabetes. Scientific information about this plant is limited. Therefore, this study investigated the antidiabetic and antioxidant activities and also the toxicity of seed extract from L. leucocephala (LLSE). Antidiabetic activity testing was carried out by giving LLSE at an oral dose of 250 mg/kg body weight to streptozotocin-induced diabetic rats daily for 6 wk. The results revealed that LLSE significantly (p < 0.05) reduced the fasting blood glucose and the blood chemistry consisting of: albumin, alkaline phosphatase (ALP) and total protein and red blood cells in the diabetic-treated rats compared to those in diabetic-untreated rats. LLSE slightly increased the serum insulin level in the diabetic-treated rats. Using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay showed that LLSE exhibited relatively low antioxidant activity with the concentration of a sample required for 50% scavenging of the DPPH free radical of 839.56 ± 37.34 mg/mL compared to vitamin C (1.48 ± 0.07 mg/mL). A spectrophotometric technique, based on the Folin-Ciocalteau reagent, revealed that the total phenolic compound contents of LLSE were 37.38 ± 0.49 mg GAE/g. LLSE at doses of 1000 mg/k body weight, 1500 mg/k body weight and 2000 mg/k body weight did not produce any symptoms of acute toxicity or mortality in the rats. These results indicated that seed extract from L. leucocephala has antidiabetic and antioxidant activities. The antioxidant activity is likely due to the phenolic content. An application of this extract should be considered as it can affect renal function by reducing the levels of albumin, ALP and total protein.